Firm Size, Economic Situation and Influence Activities - Matthias Kräkel (University of Bonn, Bonn Graduate School of Economics (BGSE), 2006)
This paper discusses the optimal firm size in the presence of influence activities, and the level of individual rent-seeking dependent on the economic situation of the firm. Since size has a discouraging effect on the level of individual rent-seeking but also a quantity effect as the number of rent-seekers increases, the interplay of both effects determines whether the employer chooses an inefficiently small or large firm size. In the given setting, a bad economic situation leads to both a higher probability of a substantial loss and a reduction of productivity. The productivity effect and the two other effects together determine the optimal level of individual rent-seeking.
Keywords: L2; D2; M2; 330; economic situation; firm size; influence activities; politicking; rent-seeking